An assessment of the smallholder rice farming households' vulnerability to climate change and variability in the Mekong delta region of Vietnam. Issue 8 (3rd August 2021) - Ho, Tien D. N.; Kuwornu, John K. M.; Tsusaka, Takuji W.; Nguyen, Loc T.; Datta, Avishek
ABSTRACT: This study assessed the livelihood vulnerability of rice farming households in Can Tho, Dong Thap, and Tien Giang provinces in the Mekong delta region (MDR) of Vietnam using primary data collected from 405 rice farmers, and the Livelihood Vulnerability Index ( LVI ) and LVI-Intergovernmental Panel on Climate Change ( LVI-IPCC ) approaches. The calculated LVI revealed that rice farming households were vulnerable in terms of the social network, livelihood strategies, natural disaster and climate variability, and food security. The LVI-IPCC revealed that Tien Giang province was the most vulnerable to climate change and variability, followed by Can Tho province. The findings suggest that intervention programmes strengthen communication networks among farmers and those local governments and other organisations to provide subsidies and training courses for farmers to cope with climatic events, as well as create more opportunities for them to diversify their income sources.